PENGARUH LABA KOTOR, LABA OPERASI, LABA BERSIH DALAM MEMPREDIKSI ARUS KAS DI MASA MENDATANG PADA PERUSAHAAN LQ 45 PADA TAHUN 2017-2021 - Zega, Winda Putridayanti; Sari, Asih Purwana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of gross profit, operating profit and net profit in predicting future cash flows at LQ 45 companies in 2017-2021. In this study a sampling technique was used, namely purposive sampling technique. So that the samples obtained were in accordance with the criteria, namely 13 LQ 45 companies in 2017-2021 with a total of 65 observational data for 5 years of observation. The data collection technique used is secondary data taken through the official website of the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS software. The results of this study indicate that gross profit has a significant positive effect on future cash flows. Operating profit has a negative effect on future cash flows. Net profit has a significant positive effect on future cash flows and then has a significant effect on gross profit, operating profit and net profit on future cash flows simultaneously.